Crecimiento, Fenología y acumulación de biomasa en una población experimental de maíz (Zea mays L.), en Barva, Costa Rica. (ING) - Hilje, Luko (1987)
Number of leaves and total biomass of a corn population increased non-linearly during the growing season; increase in plant height followed a sigmoid pattern. Reproductive structures, evident ten weeks after planting, contributed to the largest proportion of biomass gain at the end of the growing season. Although tasseling and silking are defined events in the phenology of corn, their appearance could not be predicted by means of either calendar days or degree-days in this study.